The roles and competencies of welfare commissioners supporting children with developmental disorders and their families expected by Japan’s public health nurses - Chihiro Kawai; Tomoya Yokotani; Feni Betriana; Hirokazu Ito; Yuko Yasuhara; Tetsuya Tanioka; Kenji Mori (Belitung Raya Foundation, Indonesia, 2023)
Background: Public Health Nurses (PHNs) collaborate with community volunteer welfare commissioners to support children with developmental disorders and their families lead a life without isolation. Objective: This study aims to clarify the roles and competencies that PHNs expect of welfare commissioners in supporting children with developmental disorders and their families. Methods: An online survey was administered through Survey Monkey© to 220 PHNs working in Japanese municipalities using an independently developed questionnaire regarding the roles and competencies of welfare commissioners supporting children with developmental disorders and their families expected by PHNs. Exploratory Factor Analysis (EFA) was performed to simplify the data structure and enhance understanding. The reliability of the scale was confirmed using Cronbach’s α. Differences due to PHN attributes (e.g., experience collaborating with welfare commissioners) were analyzed using Welch’s t-test. This study was conducted between April and September 2021. Results: The highest scoring items were, for the role, “a welfare commissioner’s role is to pass on accurate information to their successor,” and for competencies, “a necessary competency for a welfare commissioner is to protect the information about children with developmental disorders, and their families learned during one’s work.” The EFA results revealed a two-factor structure for role items: Factor 1, “Supporting children with developmental disorders and their families and preventing abuse,” and Factor 2, “Connecting to social resources.” Competency items were also found to have a two-factor structure: Factor 1, “Understanding the position of children with developmental disorders and their families and connecting with local residents,” and Factor 2, “Understanding developmental disorders and supporting them based on assessment.” A comparison of the attributes of PHNs showed no significant differences. Conclusion: PHNs feel welfare commissioners should pass on the information and protect confidentiality when supporting children with developmental disorders and their families. Furthermore, PHNs expect welfare commissioners to connect children with developmental disorders and their families to the community, prevent abuse, and provide support based on assessment. PHNs had the same expectations regarding the roles and competencies of welfare commissioners regardless of their own attributes.